A Study on Friction Stir Processing Effected on Hardness and Tensile Properties When Single Pass and Double Pass Is Considered Using Al 6061 And Steel Material - Hari Goud (International Journal of Fracture Mechanics and Damage Science, 2024)
The principle of friction stir welding was initially employed to build the emerging technology known as friction stir processing, or FSP. FSP has shown to be a successful method of developing face mixes and increasing the material's mechanical parcels. Aluminum blends are among those accoutrements over which the FSP can be performed successfully. The study comprised the careful processing of steel and Al 6061 samples using both single and double FSP passes. Grain homogeneity and refinement had been significantly improved in the treatment zones, according to microstructural study. The outcomes showed that, in comparison to single pass FSP, double pass FSP produced larger gains in hardness and yield strength. friction stir processing has become the latest updated in the technology to increase the strength of materials used, here we can use either two different alloys or even an alloy as the base material and any other alloy, metal or composite material as the secondary material. This paper examines the state of knowledge and the ongoing efforts of FSP about blends of aluminum 6000 series. The crushing force of face mixtures is the major emphasizing. The experimental setup included varying the number of passes to assess their influence on the material properties. Microstructural analysis revealed significant grain refinement in the processed zones, contributing to variations in hardness and tensile propertiesThis composition helps us to study the processing of aluminum 6 series alloy using powdered steel in single pass and double pass using FSP. The results suggest that the performance of steel and Al 6061 may be greatly improved by adjusting the number of FSP passes, thus rendering this approach viable for industrial applications requiring exceptional strength.
Keywords: Al 6 series; Friction stir processing; Hardness; double pass welding; single pass welding; steel material